Cervical Dystonia in Pregnancy in a Woman with Three Kidneys, Uterine and Ocular Anomalies - Madu, AE (Nepal Journal of Obstetrics and Gynaecology, 2014)
Pregnancy complicated by rare or uncommon neurological disorders of movement can present to the obstetrician/ staff andthus present a challenge to the routine obstetric care staff. A case of a 30 - year- primigravida with cervical dystonia, ocular,genital and renal tract anomaly is presented with a literature review. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 54-56 DOI: http://dx.doi.org/10.3126/njog.v8i2.9772